Reflexões epistemológicas sobre filosofia das ciências e docência universitária à luz da teoria da complexidade: uma pesquisa qualitativa pela religação dos saberes - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This master's dissertation is composed of three articles, methodologically referred to as a multipaper – compiled articles. It is a bibliographic investigation with a qualitative approach. The purpose of this study is to analyze the epistemological implications of Edgar Morin’s theory of complexity and the concept of the re-linking of knowledge, in articulation with other theories of knowledge, in criticizing the foundations of Cartesian-positivist science. The articles address, as noted by Severino (2013, p. 182), “aspects that have not yet been properly explored or that provide new clarifications on issues under discussion in the scientific community.” To this end, rigorous methodological procedures were adopted in selecting academic works relevant to the scope of the research, according to the criteria proposed by Prodanov and Freitas (2013) and Severino (2013). In this regard, the selected works stand out for their theoretical relevance, the nature of the topics addressed, the areas in which they are situated, and the recognition they have received within the scientific community. This selection aims to foster inferences and reflections that support epistemologically consistent debates, contributing to the construction of a university epistemology oriented toward the promotion of new research. In this context, Paper I proposes a conceptual introduction to epistemology and the philosophy of science, articulating critiques of contemporary sciences from the perspective of Edgar Morin’s theory of complexity. Paper II deepens the epistemic discussion by analyzing the dialogical, recursive, and hologrammatic principles, with an emphasis on the proposal of the re-linking of knowledge. Finally, Paper III discusses epistemological implications in the context of university teaching, exploring the applicability of the re-linking of knowledge to pedagogical practice in higher education. From a methodological perspective, it is acknowledged that the qualitative approach involves personal, political, and social dimensions that escape a strictly neutral structure, as pointed out by Bogdan and Biklen (1994). Thus, the conclusions are not subject to interpretive rigidity, allowing for multiple forms of understanding reality and the legitimacy of different data collection and analysis methods – a perspective that dialogues with the complexity proposed by Morin (1990) and aligns with Severino’s (2013) reflections, who proposes an epistemology capable of embracing multiple interpretations and distancing itself from the pursuit of absolute truths in science.
Epistemological reflections on the philosophy of science and university teaching in light of complexity theory: a qualitative study on the reconnection of knowledge
Keywords: Conhecimento; Epistemologia; Filosofia; Edgar Morin; Crítica paradigmática; Docência universitária; Complexidade moriniana; Hologramática moriniana; knowledge; Philosophy; Paradigmatic critique; University teaching; Morinian complexity; Morinian hologrammatics; FUNDAMENTOS DA EDUCACAO::FILOSOFIA DA EDUCACAO